The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1111/j.1365-2788.2006.00928.x
|View full text |Cite
|
Sign up to set email alerts
|

Child, parent and family factors as predictors of adjustment for siblings of children with a disability

Abstract: The results revealed that the family level of risk and resilience factors were better predictors of sibling adjustment than siblings' own experiences of stress and coping resources, highlighting the importance of familial and parental contributions to the sibling adjustment process. The implications of these results for the design of interventions and supports for siblings are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
92
2
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(110 citation statements)
references
References 43 publications
7
92
2
7
Order By: Relevance
“…For example, family characteristics such as socioeconomic status (Macks & Reeve, 2007;Petalas et al, 2009), family size (Kaminsky & Dewey, 2002;Labay & Walco, 2004) and parental stress (Giallo & Gavidia-Payne, 2006) have been shown to predict emotional and internalising problems in siblings of children with a DD. In addition, research has shown that siblings' psychological well being is, at least in part, affected by characteristics of their disabled brother/sister, especially their behavioural problems.…”
Section: Introductionmentioning
confidence: 99%
“…For example, family characteristics such as socioeconomic status (Macks & Reeve, 2007;Petalas et al, 2009), family size (Kaminsky & Dewey, 2002;Labay & Walco, 2004) and parental stress (Giallo & Gavidia-Payne, 2006) have been shown to predict emotional and internalising problems in siblings of children with a DD. In addition, research has shown that siblings' psychological well being is, at least in part, affected by characteristics of their disabled brother/sister, especially their behavioural problems.…”
Section: Introductionmentioning
confidence: 99%
“…Braća i sestre dece sa ometenošću imaju više emocionalnih problema i problema u ponašanju i odnosima sa vršnjacima od dece koja nemaju brata/sestru sa ometenošću. Problemi u psihološkom prilagođavanju ove dece pod nepovoljnim su uticajem nivoa stresa njihovih roditelja, za koji je utvrđeno da je viši u odnosu na populacione norme (Giallo, Gavidia-Payne, 2006). Takođe, utvrđeno je da braća i sestre dece sa ometenošću snažnije doživljavaju porodične konflikte i svakodnevni stres i teže se nose sa njima, u odnosu na decu čija braća/sestre pripadaju tipičnoj populaciji (Nixon & Cummings, 1999) Većina žena detaljno razmatra sopstvena moralna uverenja i vrednosti pre pristupanja prenatalnom skriningu (Williams et al, 2005).…”
Section: Dileme U Procesu Odlučivanja O Nastavku/prekidu Trudnoćeunclassified
“…Indeed, children who have noticeable visible facial differences are thought to be especially vulnerable to stigmatisation (7) and research has shown that the severity of a condition is often linked to adjustment outcomes in children (8). However, it has also been proposed that contextual factors within the family unit can play an important role in influencing how an individual and their family adapts to the stressors which they are faced with (9). The Family Resiliency Model of Stress, Adjustment and Adaptation has been used extensively to investigate the recovery factors involved in chronic childhood conditions.…”
Section: Introductionmentioning
confidence: 99%